The Effectiveness of Watching Movie in Improving Students’ Listening Comprehension at SMAN 2 Pekanbaru - Daffa Putra; Afrianto; Eliwarti (Lembaga Anotero Scientific, 2024)
This study investigates the effectiveness of watching movies as a method to improve students' listening comprehension at SMAN 2 Pekanbaru. The research aimed to explore whether incorporating movies into English language teaching can enhance students' ability to understand spoken English in various contexts. The study employed a quasi-experimental design, involving two groups of students: an experimental group, which was exposed to movie-based listening activities, and a control group, which followed traditional listening exercises. Pre- and post-tests were administered to assess the students' listening comprehension skills. The findings revealed that the experimental group showed significant improvement in their listening comprehension compared to the control group, suggesting that watching movies can be an effective strategy in enhancing students' listening skills. This research contributes to the ongoing exploration of innovative methods in language teaching, offering insights into the potential benefits of integrating multimedia resources in the classroom.